Digestive proteases and carbohydrases along the alimentary tract of the stargazer, Uranoscopus scaber Linnaeus, 1753 - PAPOUTSOGLOU, E.S.; LYNDON, A.R. (Mediterranean Marine Science, 2006)
Digestive enzyme activity and capacity (activity x tissue weight) for protein (total protease assay, 25° C) and carbohydrates (total carbohydrase and alpha-glucosidase assay at 5, 18 and 25° C) was investigated for the carnivorous stargazer, Uranoscopus scaber along its digestive tract. Results indicated that whole gut total protease activity was highest at pH 1.5 (P<0.05) (25° C) in U. scaber, (6.64±2.55 mg tyrosine per g digestive tract per minute, pH 1.5). Total protease activity was apparent mainly in the stomach at pH 1.5 (9.73±3.3), and to a lesser degree in the anterior intestine (11.15±1.5, pH 10.0) and pyloric caeca (4.92±2.06, pH 10.0), especially at pH 9.0 and 10.0. Furthermore, 60% of total capacity for protein digestion derives from the stomach region, which takes up 65% of the digestive tract. Total carbohydrase activity and capacity levels were very low compared to other carnivorous teleosts, indicating very low tendency for complex, large molecular weight carbohydrate digestion. However, alpha-glucosidase levels were higher, a fact which combined with relevant data for other marine carnivorous teleosts suggests a possible role of disaccharide in relation to marine carnivorous fish dietary carbohydrate inclusion.